2021
DOI: 10.1002/nop2.923
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery protocols in patients undergoing pancreatic surgery: An umbrella review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Our results confirmed these findings and showed that patients undergoing pancreatic surgery do indeed consider hospitals as an unwelcoming space for mobilisation and early recovery. Early removal of drains, as one component of ERAS, is important to promote optimal postoperative recovery 46. Hence, health professionals may remove unnecessary drains early according to the patients’ clinical condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirmed these findings and showed that patients undergoing pancreatic surgery do indeed consider hospitals as an unwelcoming space for mobilisation and early recovery. Early removal of drains, as one component of ERAS, is important to promote optimal postoperative recovery 46. Hence, health professionals may remove unnecessary drains early according to the patients’ clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Early removal of drains, as one component of ERAS, is important to promote optimal postoperative recovery. 46 Hence, health professionals may remove unnecessary drains early according to the patients’ clinical condition. It is not surprising that a lack of staffing is a barrier to patients’ successful participation in mobilisation, and this barrier is not easily changeable.…”
Section: Discussionmentioning
confidence: 99%